Description of Benson Relaxation Tehnique on Anxiety at Student of Diploma Nursing Mulawarman University - Samsugito, Iwan; Dzulhijjania, Nadya Armanur Islamy; Nopriyanto, Dwi (Jurnal Kesehatan Pasak Bumi Kalimantan, 2022)
Background: Anxiety is a condition that can develop in a person in a life-threatening situation and can serve as a warning sign that he must be prepared to face the situation. Anxiety can be characterized by feelings of worry, fear, and tension, as well as physiological changes. Objective: To find out the application of Benson's relaxation technique to decrease anxiety in PSDK Unmul students while practising at the hospital. Methods: In this Scientific Writing research, the author uses a qualitative descriptive research design with a case study approach to students who have feelings of anxiety during hospital practice. The phenomenon to be studied is the level of anxiety before and after Benson Relaxation therapy is performed on students. Results: The study's results before being given Benson relaxation showed that many respondents experienced anxiety with moderate category 8, and some students experienced severe anxiety category 2. After Benson's relaxation, 6 respondents were not anxious, 2 were mildly anxious, 1 was moderately anxious, and 1 was severe anxious; this indicates that Benson's relaxation can reduce anxiety levels in practising PSDK students. Benson relaxation can relax the body and mind and reduce brain waves, stimulating the release of endorphin hormones. Conclusions and suggestions: Benson relaxation can reduce anxiety levels in PSDK Unmul students practising at the hospital. Benson relaxation measures can be applied to students who practice in the hospital, mainly level 1 students. Therapy can be done independently or by lecturers to reduce anxiety.Keywords: Benson Relaxation, Anxiety, Practice